2011
DOI: 10.1684/agr.2011.0473
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and poverty: The case of the Office du Niger in Mali

Abstract: Irrigation and poverty: The case of the Office du Niger in MaliSurveys were carried out in 2004 in the Office du Niger in Mali, to assess the contribution of irrigation schemes to poverty reduction. Results show that the situation is better in the Office du Niger than in any of the other rural areas in Mali, including the Ségou region. The investments in irrigation schemes have contributed to strong agricultural growth and a reduction in poverty amongst smallholder farmers. However, this positive effect is ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 5 publications
0
7
0
10
Order By: Relevance
“…Drainage problems affect water management in the plot, which influences the "abundance of tillers per hill," weed management and fertilizer losses. Bélières et al (2011) showed that farmers' difficulties in accessing inputs, credit, and equipment, and constraints related to water management contribute to the drop in productivity in the Office du Niger area.…”
Section: Indirect "Factors"mentioning
confidence: 99%
“…Drainage problems affect water management in the plot, which influences the "abundance of tillers per hill," weed management and fertilizer losses. Bélières et al (2011) showed that farmers' difficulties in accessing inputs, credit, and equipment, and constraints related to water management contribute to the drop in productivity in the Office du Niger area.…”
Section: Indirect "Factors"mentioning
confidence: 99%
“…Irrigation's positive impact on income is undeniable, despite the fact that poverty still needs to be alleviated in such irrigated areas, especially in sub-Saharan Africa (Bélières et al 2011). The flip side of this dependence on external sectors, on the other hand, is that farmers with irrigated lands enjoy a higher standard of living compared to those with rainfed systems, when supply and marketing conditions are favorable.…”
Section: Access To Water For Agriculture: Beyond Technologies Policymentioning
confidence: 99%
“…A lmost all farming units are family farms (Coulibaly, Bélières and Koné 2006;Bélières et al 2011) in which all (or nearly all) the agricultural work is performed by members of the manager's family. hey number between 22,635 (our estimate obtained by dividing the total irrigated area of the zone (86,201 ha) by the average size of family farms according to our survey (3.81 ha)) and 43,000 (Oice du Niger's estimate (2010), probably overstated as a farmer with land in two villages is counted twice, and some peasant families pretend to be separated in order to try to have access to more land).…”
Section: Family Farms Almost Exclusivelymentioning
confidence: 99%